Acquiring Reading Skills in a Foreign Language - Inma Piquer (Universidad Autónoma de Madrid, 2016)
Reading in a foreign language means both, a challenge and a need to citizens from a plurilingual society. In Catalonia, plurilingualism has been an educational priority and a social aim for several decades. To guarantee the success of this procedure, teachers have the responsibility to provide their students with contexts and resources like dialogic reading, debates, literary gatherings, cooperative work and other collaborative activities for guiding students and help them to achieve reading literacy.